Multiple Targets of the Canonical WNT/β-Catenin Signaling in Cancers - Lecarpentier, Yves; Schussler, Olivier; Hébert, Jean-Louis; Vallée, Alexandre (Frontiers in Oncology, 2019)
Abstract Canonical WNT/catenin signaling is involved in most of the mechanisms that lead to the formation and development of cancer cells. It plays a central role in three cyclic processes, which are the cell division cycle, the immune cycle and circadian rhythms. When the canonical WNT pathway is upregulated as in cancers, the increase in -catenin in the nucleus leads to activation of the expression of numerous genes, in particular CYCLIN D1 and cMYC, where the former influences the G1 phase of the cell division cycle, and the latter, the S phase. Every stage of the immune cycle is disrupted by the canonical WNT signaling. In numerous cancers, the dysfunction of the canonical WNT pathway is accompanied by alterations of the circadian genes (CLOCK, BMAL1, PER). Induction of these cyclic phenomena leads to the genesis of thermodynamic mechanisms that operate far from equilibrium, and that have been called “dissipative structures”. Moreover, in cancers, upregulation of the canonical WNT pathway plays a central role in the formation of the cancer stroma which contains many myofibroblasts. Their differentiation is controlled by the canonical WNT /TGF-signaling. Myofibroblasts present ultraslow contractile properties due to the presence of the non-muscle myosin IIA. Myofibroblats also play a role in the inflammatory processes, often found in cancers and fibrosis processes. Finally, upregulated canonical WNT deviates mitochondrial oxidative phosphorylation towards the Warburg glycolysis metabolism, which is characteristic of cancers. Among all these cancer-generating mechanisms, the upregulated canonical WNT pathway would appear to offer the best hope as a therapeutic target, particularly in the field of immunotherapy.